COMPARISON BETWEEN NEBULISATION OF MGSO4 20 MG/KGBW WITH KETAMINE 0.5 MG/KGBW ON THE INCIDENT OF POST-OPERATIVE SORE THROAT DUE TO ENDOTRACHEAL INTUBATION IN PATIENTS UNDERGOING GENERAL ANESTHESIA IN DR. HASAN SADIKIN HOSPITALS BANDUNG - Widianto Sudjud, Reza; Erias Erlangga, Muchammad; Akbar, Diki (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Post Operative Sore Throat (POST) is a Symptoms often experienced by patients after surgery under general anesthesia and endotracheal intubation. The incidence of POST is between 21-71.8. POST causes discomfort to patients which can prolong hospital stay. In this study, a comparison was made between MgSO4 nebulization 20 mg/ KgBW and ketamine nebulization 0.5 mg/ KgBW on the incidence of POST after general anesthesia at RSUP Dr. Hasan Sadikin Bandung . This study used a double blind randomized controlled trial design. 72 elective surgery patients were randomly divided into 2 groups. Group M was given MgSO4 nebulization while group K was given ketamine nebulization. Nebulization was performed 15 minutes before induction of general anesthesia. POST monitoring was performed at 1, 4 and 24 hours after extubation using POST scoring. In this study, it was found that the incidence of POST in group M, namely the 1st hour of 13.5, the 4th hour of 10.8 and the 24th hour of 0 was lower than that in group K, namely the 1st hour of 28.5, the 4th hour of 32.5 and the 24th hour of 0. Statistical test results p0.033 showed a significant difference in group M better than group K at the 4th hour in reducing the incidence of POST. MgSO4 and ketamine have antinociceptive and anti-inflammatory effects with the mechanism of action of blocking NMDA receptors that inhibit calcium influx that avoids central sensitization. MgSO4 also has a muscle relaxing effect and reduces airway mucus secretion, thus reducing the risk of trauma during endotracheal intubation. The conclusion of this study is that MgSO4 nebulization shows a lower incidence of POST than ketamine nebulization.